An electrochemical sensing platform based on a modified carbon paste electrode with graphene/Co3O4 nanocomposite for sensitive propranolol determination - Parisa Karami-Kolmoti; Reza Zaeimbashi (ADMET and DMPK, 2023)
A simple and sensitive method for the determination of propranolol using a modified carbon paste electrode (CPE) with graphene/Co3O4 nanocomposite (Gr-Co3O4 NC/CPE) was presented. The electrochemical measurements of propranolol are studied using differential pulse voltammetry (DPV), cyclic voltammetry (CV) and chronoamperometry (CHA). The Gr-Co3O4 NC/CPE exhibits excellent catalytic activity towards the electrochemical oxidation of propranolol in phosphate buffer solution (PBS) of pH 7.0. The Gr-Co3O4 NC/CPE facilitates the determination of propranolol in the concentration range 1.0–300.0 μM and a detection limit and sensitivity of 0.3 μM. and 0.1275 μA/μM were achieved.